Wind Speed Profiles and Pressure Coefficients Obtained in the Wind Induced Damage Simulator for Silsoe Cube Model - Singh, Jaskirat (Université d'Ottawa / University of Ottawa, 2020)
Hazardous winds, such as tornadoes and hurricanes, have a great impact on civil engineering structures and cause significant social and economic disturbances. The wind speed and pressure tested in the conventional wind tunnel experiments are much smaller than the actual wind speed and pressure measured in the field. Therefore, the Wind-induced Damage Simulator (WDS) was constructed at the University of Ottawa to overcome the wind speed limitations of wind tunnels and to simulate different types of wind speed profiles. WDS is an isolated cubic box with dimensions 3.65m x3.65 m and 3.0 m height, with multiple inlets on the side faces of the testing chamber and an outlet on the top side. This unique equipment creates a controlled environment for studying wind speed profiles in a confined space, by regulating the air flow with the aid of an attached industrial blower. To measure the simulated wind velocities inside the WDS and to obtain the wind speed profile in the testing chamber, Aeroprobe (12- Hole Probe) sensor was used for different combinations of opened inlets and at four different locations. The data collected from the Aeroprobe was processed by the use of the Aeroflow 2.7.5.7346 software, to get the velocity of wind in three different directions (u, v and w) and the mean velocity at a single point. After determining the mean velocity at different heights and RPM values at all four positions, Matlab software was used to determine the wind profile and the spectra of the turbulence intensities and these were compared for different heights at the four investigated locations and for various rotations per minute (RPM) values (400 to 800 RPM) for controlling the blower. Once the flow characterization was completed, the wind-induced pressure for three models of the Silsoe Cube were measured as a part of the second phase of the test. The current experiment employed 3 different scales of Silsoe cube: 1:40, 1:30 and 1:20, while the pressure coefficients were determined at 16 different points along a vertical line crossing the faces of the cube. A pressure taps system with 16 channels and a Scanivale pressure scanner were used to measure the pressure at 16 different positions on the cube. Matlab software was used to determine the pressure coefficients from the data measured by pressure taps. The pressure coefficienst for the Silsoe Cube were plotted and compared for the three different scales. Also, for determining the best scale to be used in future experiments. The pressure coefficients of the 3 different scaled model of Silsoe Cubes was compared with full-scale data reported in the literature for the same structure. Based on the results obtained from the experiments, recommendations for the best location in the testing chamber for the future experiments employing the WDS were formulated.
Keywords: WDS; Pressure coefficients; Wind speed profile; SIlsoe cube; Aeroprobe